Implementasi Tugas Sekretariat Dewan Perwakilan Rakyat Daerah dalam Mendukung Pelaksanaan Fungsi DPRD dalam Pembentukan Peraturan Daerah di Kabupaten Tanjung Jabung Barat - Yanti, Herma; Saputra, Warfian; Aditya, Dickie (Wajah Hukum, 2024)
As a regional apparatus tasked with supporting the implementation of the DPRD's duties and functions, the DPRD Secretariat is expected to be able to implement these tasks optimally, especially supporting the implementation of the DPRD's main function in forming Regional Regulations. This research aims to see how it is implemented at the West Tanjung Jabung Regency DPRD Secretariat and what factors influence its implementation. The research type is empirical legal research with a socio legal research approach. Primary data was collected through interviews with respondents from the DPRD Secretariat who were determined using purposive sampling, as well as studying documents that had been compiled and were available at the DPRD Secretariat related to the implementation of programs and activities that had been carried out to support the implementation of the DPRD's functions in the formation of Regional Regulations. 2021 to 2023. Meanwhile, secondary data was collected from library sources, namely related laws and regulations, books and journals. The results show that the implementation of the tasks of the DPRD Secretariat of West Tanjung Jabung Regency is not optimal every year. The factors that influence this are mainly the limited human resources of the DPRD Secretariat and several other factors that need to be followed up for future improvements.